Β-Blockers and Plasma Renin Activity in Hypertension. Issue 5897 (12th January 1974) - Stokes, G. S.; Weber, M. A.; Thornell, I. R.
Abstract : Long-term treatment with propranolol was shown to produce a sustained suppression of the renin-aldosterone system in hypertensive patients, despite concurrent diuretic treatment. However, the antihypertensive effect of this treatment correlated poorly with its effects on plasma renin activity and urinary aldosterone excretion. When prindolol, another β-adrenergic blocking drug, was substituted for propranolol, blood pressure control was retained, but there was a prompt rise in plasma renin activity, which was not attributable to changes in electrolyte balance. These observations suggest that the antihypertensive action of propranolol and other β-blockers does not result from their effects on plasma renin activity.